2018
DOI: 10.1002/jbmr.3549
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Canonical β-Catenin Signaling During Osteoblast Differentiation Contributes to Osteopenia in Progeria

Abstract: Patients with Hutchinson-Gilford progeria syndrome (HGPS) have low bone mass and an atypical skeletal geometry that manifests in a high risk of fractures. Using both in vitro and in vivo models of HGPS, we demonstrate that defects in the canonical WNT/β-catenin pathway, seemingly at the level of the efficiency of nuclear import of β-catenin, impair osteoblast differentiation and that restoring β-catenin activity rescues osteoblast differentiation and significantly improves bone mass. Specifically, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…Quantitative RT-PCR revealed that the expression level of TCF-1 was significantly reduced by the expression of progerin but not lamin A ( Figure 1(d )). Interestingly, the expression of Wnt/β-catenin-inducible genes is reported to be decreased in cells of HGPS patients [ 13 , 14 ]. We suggest that the decrease of nuclear F-actin by progerin expression contributes to the misregulation of genes in HGPS cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative RT-PCR revealed that the expression level of TCF-1 was significantly reduced by the expression of progerin but not lamin A ( Figure 1(d )). Interestingly, the expression of Wnt/β-catenin-inducible genes is reported to be decreased in cells of HGPS patients [ 13 , 14 ]. We suggest that the decrease of nuclear F-actin by progerin expression contributes to the misregulation of genes in HGPS cells.…”
Section: Resultsmentioning
confidence: 99%
“…Gene expression is also affected in HGPS cells. Notably, Wnt/β-catenin signaling, known to be a fundamental pathway, is diminished in HGPS cells [ 13 , 14 ]. It has been suggested that the suppression of Wnt/β-catenin signal activity and decreased levels of Wnt/β-catenin-responsive gene expression is the cause of bone defects in HGPS [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…47 Microcomputed tomography Femurs were dissected from 8-to 12-week-old female WT and LPL −/− mice and processed as described. 71 Three-dimensional Micro-CT was performed on femurs (n = 5-6) using a SkyScan 1172 (Bruker, Kontich, Belgium) at 60 kV (167 µA) and a 9.91 µm voxel size, as described. 72,73 The skeletal parameters assessed by micro-CT followed published nomenclature guidelines.…”
Section: Migration Assaysmentioning
confidence: 99%
“…Teriparatide treatment increases bone mass in Lrp5 KO mice mimicking humans with osteoporosis pseudoglioma syndrome from loss of function LRP5 mutations (88,89). Similarly, anti-sclerostin antibody treatment increases bone mass in mutant mouse models with low bone mass from gene disruptions (90) of Col1a1 (91, 92), Col1a2 (93, 94), Crtap (95), Dmp1 (96), Lrp5 (97), and Zmpste24 (98). Mechanistic hypotheses can be tested, such as periostin treatment retarding skull suture fusion in heterozygous Twist1 mice with craniosynostosis (99).…”
Section: Mouse Modelsmentioning
confidence: 99%